RANCANG BANGUN APLIKASI SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEMILIHAN DESTINASI PARIWISATA SUMATERA BARAT MENGGUNAKAN METODE ELECTRE - Dony Novaliendry; Yuli Pusparani (Jurnal Teknologi Informasi dan Pendidikan, 2019)
Tourism is one of the activities carried out by humans that has a purpose as entertainment. Human who travel are referred to as tourist. West Sumatra Province is one of the regions with the best tourism is sea tourism and land tourism. Marine tourism consists of beach tourism, island tourism and lake tourism, while mainland tourism consists of tourist panorama, mountain tours, hill tours and others. However, only a portion of West Sumatra's tourist attractions are known to tourists, because of this information is obtained so that there are still many tourist attractions in West Sumatra unknown to tourists from outside the West Sumatra region. To overcome this problem, a system is needed that can be used to support the electoral decision-making process in West Sumatra. This system is built on the Web, using the PHP programming language and Laravel Framework and MySQL as a Database. The method used in this system is the Elimination of Et Choix Traduisant la Realite (ELECTRE). The use of Elimination Et Choix Traduisant la REalite (ELECTRE) can help provide information in West Sumatra, which is in accordance with the wishes of tourists according to the specified criteria. With the help of this system, the information obtained will make it easier for tourists to find tourist attractions.